2009
DOI: 10.1002/em.20537
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and oxidative stress in human liver cell L‐02 caused by surface water extracts during drinking water treatment in a waterworks in China

Abstract: Because of the daily and life-long exposure to disinfection by-products formed during drinking water treatment, potential adverse human health risk of drinking water disinfection is of great concern. Toxicological studies have shown that drinking water treatment increases the genotoxicity of surface water. Drinking water treatment is comprised of different potabilization steps, which greatly influence the levels of genotoxic products in the surface water and thus may alter the toxicity and genotoxicity of surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…The comet assay and SOS/umu test are generally used to detect the DNAdamage effects of various compounds and complex water samples [22,25,32]. In previous studies using the comet assay, the extracts of raw water and chlorinated drinking water from Hanjiang River induced the DNA-damage effects [17,28]. In the present study, the results of SOS/umu test showed that all water samples in two different sampling times induced the DNA-damage effects, which were consistent with previous studies.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The comet assay and SOS/umu test are generally used to detect the DNAdamage effects of various compounds and complex water samples [22,25,32]. In previous studies using the comet assay, the extracts of raw water and chlorinated drinking water from Hanjiang River induced the DNA-damage effects [17,28]. In the present study, the results of SOS/umu test showed that all water samples in two different sampling times induced the DNA-damage effects, which were consistent with previous studies.…”
Section: Discussionsupporting
confidence: 94%
“…Water extracts were prepared using solid-phase extraction that has been described in detail in our previous study [28]. In brief, water samples were extracted using Amberlite XAD-2 resins that were pre-cleaned with methanol, hexane, acetone, and dichloromethane.…”
Section: Water Sample Collection and Preparationmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) has categorized formaldehyde as a leukemogenic agent[57]. Formaldehyde is capable of cross-linking DNA as well as proteins on their amino groups[57].…”
Section: 0 Overview Of the Evidence For Oxidative Stress In Cwas Anmentioning
confidence: 99%
“…These organosulfur compounds are commonly constituted of one isothiocyanate (-N=C=S) moiety. ITCs have particularly received great attention because they show health promoting properties such as anticancer, antioxidant as well as induction of phase 2 detoxifying enzymes [4]. Several works in literature dedicated to identify and evaluate experimentally the antioxidant potential of ITCs available in different natural products such as Emeraude cauliflower [5].…”
Section: Introductionmentioning
confidence: 99%